2001
DOI: 10.1055/s-2001-18841
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Stevioside on Calcium Influx to Produce Antihypertension

Abstract: Stevioside is a sweet-tasting glycoside occurring abundantly in the leaves of Stevia rebaudiana (Compositae). It has been used popularly in Japan and Brazil as a sugar substitute for decades. Previous study has shown that it lowered blood pressure in spontaneously hypertensive rats (SHRs) when administered intravenously. This study shows that intraperitoneal injection of stevioside 25 mg/kg also has antihypertensive effect in SHRs. In isolated aortic rings from normal rats, stevioside could dose-dependently re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 4 publications
6
78
0
5
Order By: Relevance
“…Thus, stevioside was not able to reduce the increment caused by L-NOARG and ODQ in the vasoconstriction induced by norepinephrine in endothelium-intact aortic ring preparations because in such experimental conditions, in contrast with that utilizing the endotheliumdenuded preparations, endothelin could also be causing vasoconstrictor effects. This hypothesis is strengthened by data obtained in previous studies that had indicated that the vasorelaxant effect of stevioside is dependent on the blockade of Ca ++ channels (Lee et al, 2001), and that such mechanism of action of these drugs is not able to reverse the vasoconstriction induced by endothelin (Vanhoutte et al, 1989). In contrast, the increment caused by L-NOARG and ODQ in the vasoconstriction induced by cellular depolarization with KCl would be the result of a specific reduction in NO synthesis in endothelial cells bringing about a decrease in the inhibitory effect of the gas and increasing the effect of endothelin on arterial smooth muscle cells.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, stevioside was not able to reduce the increment caused by L-NOARG and ODQ in the vasoconstriction induced by norepinephrine in endothelium-intact aortic ring preparations because in such experimental conditions, in contrast with that utilizing the endotheliumdenuded preparations, endothelin could also be causing vasoconstrictor effects. This hypothesis is strengthened by data obtained in previous studies that had indicated that the vasorelaxant effect of stevioside is dependent on the blockade of Ca ++ channels (Lee et al, 2001), and that such mechanism of action of these drugs is not able to reverse the vasoconstriction induced by endothelin (Vanhoutte et al, 1989). In contrast, the increment caused by L-NOARG and ODQ in the vasoconstriction induced by cellular depolarization with KCl would be the result of a specific reduction in NO synthesis in endothelial cells bringing about a decrease in the inhibitory effect of the gas and increasing the effect of endothelin on arterial smooth muscle cells.…”
Section: Discussionsupporting
confidence: 63%
“…The concentration of norepinephrine we used had produced about 50% of maximal tension in isolated rat aortic rings preparations devoid of endothelium (Testai et al, 2005). The concentration of KCl used produced contraction of aortic rings preparations without, however, impairing the action of agents considered as possible K + channel openers (Nelson and Quayle, 1995) as such mechanism of action and/or the blockade of Ca 2+ channels might explain the vessel relaxation induced by stevioside (Lee et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…*, Significantly different from control (P<0.05), ANOVA followed by Dunnett's multiple comparison test. (Hirata et al, 1998), whereas contractions induced by PHE are mediated by an increase in Ca 2+ influx through both receptor-operated channels (Lee et al, 2001a) and voltage-sensitive channels (Eckert et al, 2000;Lee et al, 2001b (Leijten and van Breemen, 1984), whereas, the caffeine-induced contractions, which releases [Ca 2+ ]i by an (IP3)-independent mechanism (Standen et al, 1989) were unaltered. Thus, it seems likely that the vascular effects of KV involve a reduction in Ca 2+ release from In order to analyze the contribution of different types of K + channels to the KV-induced endothelium-independent relaxation in the mesenteric rings, we used agents that are known to possess a K + channel-blocking activity.…”
Section: Discussionmentioning
confidence: 91%
“…The stevioside in a dose-dependent manner relaxed the endothelium-intact and endothelium-denuded arteries in rat isolated aortic rings, contracted with vasopressin (Lee et al 2001). The stevioside-induced relaxation was not influenced by methylene blue, a guanylate cyclase inhibitor, presenting that the relaxation was not mediated by the cyclic guanosine monophosphate (cGMP)-NO pathway.…”
Section: High Blood Pressure and Cardiovascular Effectsmentioning
confidence: 83%
“…Therefore, the resulting data indicate that stevioside induces vasorelaxation primarily by inhibiting the extracellular Ca 2+ influx. Additionally, in vitro effects of stevioside showed that stevioside induces hypotension in conscious hypertensive rats (Lee et al 2001). …”
Section: High Blood Pressure and Cardiovascular Effectsmentioning
confidence: 99%